Economic shocks, food insufficiency and mental health: Evidence from the COVID-19 pandemic - Yuxuan Pan; Linlin Fan; Stephan Goetz (PLoS ONE, 2026)
Millions of Americans experienced a sudden loss of income along with hunger early in the COVID-19 outbreak. Using Household Pulse Survey data from April 23, 2020 to March 29, 2021, we find the pandemic significantly impacted both food sufficiency and mental health, with food insufficiency having a larger negative impact on mental health than income loss. We do not find a statistically significant effect of unemployment on mental health. These findings were confirmed in various sensitivity analysis. We also discover heterogeneous effects of food insufficiency, unemployment, and income loss on mental health across different socioeconomic groups. Larger effects of food insufficiency were found in mortgage paying-households, among males, and in non-metro areas, and larger effects of income loss were found in rent paying-households, among females, and in non-metro areas. These results indicate the need for effective and timely policies targeting disadvantaged groups to maintain or improve their mental well-being, as well as food sufficiency, during future economic crises and public health emergencies.